The illustrated encyclopedia of 20th century weapons and warfare T-35/Vil - Authors: Bernard Fitzsimmons (Editor); John Batchelor (illustrator) (New York Columbia House, 1971)
Intro, Coverage, Warships, Aircraft, Tanks and APCs, Small Arms, Missiles, Artillery
Keywords: 20th century; 20th century